The role of tenure in the management of trees at the community level: theoretical and empirical analyses from Uganda and Malawi - Place, Frank; Otsuka, Keijiro (International Food Policy Research Institute, 2000)
This paper examines the effects of tenure on tree management at a community level. First, several important conceptual issues arising from this particular meso-level focus are discussed. Second, a description of the key tenure and tree management issues in Uganda and Malawi is presented. In each case, data representing changes in land use and tree cover between the 1960-70s and 1990s are analyzed. In both countries, there has been significant conversion of land from woodlands to agriculture. Tree cover has been more or less maintained over time in Uganda but has decreased in Malawi. Lastly, the paper explores the relationships between tenure and tree management using econometric techniques. Tenure is found to be linked to land-use and tree-cover change in both countries, though it is not necessarily the most important factor (e.g., population pressure is the key driving force for land-use change). In Uganda, conversion of land was more rapid under the customary tenure system and tree cover on nonagricultural land better maintained under the mailo system. In Malawi there was more rapid land-use conversion and tree cover depletion where there were more changes to traditional tenure systems taking place.